Faktor-Faktor yang Mempengaruhi Kesulitan Belajar Membaca Al-Qur’an Siswa Kelas VII di MTs Salafiyah Wonoyoso - Mubarokah, Laeli; Hasyim, Fuad (IAINU Kebumen, 2024)
The problem with this research is that students are still found who have difficulty reading the Al-Qur'an. The aims of this research were: (1) to determine the ability to read the Al-Qur'an of class VIII students at MTs Salafiyah Wonoyoso Kebumen; (2) to determine the factors that influence the difficulty of students reading the Al-Qur'an for class VIII students at MTs Salafiyah Wonoyoso Kebumen. This research is in the form of qualitative research. The students studied were class VIII students at MTs Salafiyah Wonoyoso Kebumen. The method used in this research is qualitative method. Data collection uses interview, observation and documentation techniques. Meanwhile, the data analysis used is data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that; (1) students' ability in reading the Qur'an is not good, such as reading letters that should be read mad, sometimes not read long, those that should be read short are read long; (2) students' difficulties in reading the Qur'an include difficulty in distinguishing hijaiyah letters, difficulty in applying the laws of tajwid and difficulty in reading connected letters.